The Effect of Financial Performance, Risk, and Liquidity on Firm Value in the Manufacturing Industry Sector in Indonesia - Dian Firdaus; Eko Sudarmanto; Risna Amalia Hamzah (North Press, 2024)
This study investigates the effect of financial performance, risk, and liquidity on firm value in the manufacturing sector in Indonesia. Using a sample of 60 manufacturing companies listed on the Indonesia Stock Exchange, the research employs a quantitative approach with data analyzed through SPSS version 26. Financial performance was measured by Return on Assets (ROA), risk by Debt-to-Equity Ratio, and liquidity by Current Ratio. The Price-to-Book Ratio represented firm value. The results reveal that financial performance and liquidity have a significant positive effect on firm value, while risk has a negative effect. These findings suggest that manufacturing companies in Indonesia can enhance their market value by improving profitability and liquidity while effectively managing financial risk.